AVALIAÇÃO DAS CONDIÇÕES DE SAÚDE DOS CUIDADORES DE PACIENTES COM DEMÊNCIA DE ALZHEIMER - Gabriel, Katiuscia de Oliveira Francisco (2016)
Alzheimer's disease (AD) is a progressive neurodegenerative pathology that causes damage to the pathology (physical, mental and social), as well as changes in the quality of life of its caregivers / relatives. The first clinical aspect is the deficiency of recent memory, while remote memories are preserved until a certain stage of the disease, in addition to the difficulties of attention and verbal fluency. AD is the leading cause of dementia in the elderly in the West, making it clear that caring for caregivers is a way of fostering the development of communities in this context. Therefore, the present study aimed to evaluate the health conditions of caregivers of patients with AD. The research was carried out at the home of patients enrolled in the Association of Studies, Research and Assistance to Alzheimer's Patients located in the city of Guarapuava. This is an exploratory study, with a quantitative approach, carried out in the year 2015. Twenty-five elderly people diagnosed with AD and their respective caregivers participated voluntarily in this study. The data were collected with structured instrument, application of scales and performance of tests and collection of cortisol salivary test. Data codification and organization were performed in the Excel® 2007 computer program and statistical analysis by Statistica10® software. Data were analyzed through descriptive statistics, absolute and percentage frequency distribution, mean and standard deviation, and other measures. The results showed that the elderly population studied with AD is composed of 65.5% female patients with a mean age of 78 years. The 39.7% of the elderly with AD are in CDR 3, severe stage. Overload is present (48%) in caregivers, being considered moderate to severe. As a result of the overload caused by emotional changes, depression is present in this population. In the salivary cortisol test, cortisol results in morning and evening were the ones that gave a significant difference in values. On the other hand, signs and symptoms of respiratory infections show the influence of chronic stress experienced by caregivers, thus altering immunity, exacerbating immunosenescence. The quality of life of the caregivers of AD patients was altered, indicating a greater impairment, in the means of the domains functional capacity and emotional aspect. It is concluded that the severity of AD in the patient, along with age, overload, depression and stress, generated in care, contribute significantly to worsen quality of life of caregivers of AD.